2016
DOI: 10.1007/398_2016_4
|View full text |Cite
|
Sign up to set email alerts
|

Important Issues in Ecotoxicological Investigations Using Earthworms

Abstract: The importance and beneficial effects of earthworms on soil structure and quality is well-established. In addition, earthworms have proved to be important model organisms for investigation of pollutant effects on soil ecosystems. In ecotoxicological investigations effects of various pollutants on earthworms were assessed. But some important issues regarding the effects of pollutants on earthworms still need to be comprehensively addressed. In this review several issues relevant to soil ecotoxicological investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…Lower toxicity was indicated for the fungicides at higher temperatures (28 • C) but higher toxicity for the insecticides. Bandow et al [51] reported increased susceptibility of Collembola to the fungicide pyrimethanil at 26 • C compared to 20 • C. Increased toxicity of several common pesticides has been reported under increased temperatures (25 • C) [48]. Similarly, increased toxicity of three common agricultural pesticides (chlorpyrifos, dimethoate and deltamethrin) were observed under tropical temperatures (26-28 • C), even if the concentrations were not considered a risk in their study [49].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Lower toxicity was indicated for the fungicides at higher temperatures (28 • C) but higher toxicity for the insecticides. Bandow et al [51] reported increased susceptibility of Collembola to the fungicide pyrimethanil at 26 • C compared to 20 • C. Increased toxicity of several common pesticides has been reported under increased temperatures (25 • C) [48]. Similarly, increased toxicity of three common agricultural pesticides (chlorpyrifos, dimethoate and deltamethrin) were observed under tropical temperatures (26-28 • C), even if the concentrations were not considered a risk in their study [49].…”
Section: Introductionmentioning
confidence: 72%
“…Changing climate conditions can alter the toxicokinetics of toxic substances [36,45]. Several studies report the impact of different temperature regimes on the toxicity of agricultural pesticides [46][47][48][49] and metals [50] to soil organisms. These impacts vary as soil organisms respond differently to different toxins and chemicals under different temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They are present in a variety of soil horizons, abundant in contaminated soils and there are several standardized tests and molecular techniques on earthworms available [ 40 ]. Earthworms have frequently been applied in studies examining not only the effects of soil pollution but other anthropogenic stressors as well, by analyzing a suite of reliable and sensitive biomarkers at the molecular and cellular level [ 38 , 39 ]. Earthworms have also been found to exhibit remarkable tolerance to soils with high pollution burdens and were able to thrive and maintain abundant populations even in soils containing metal levels that significantly exceed toxic effect concentrations [ 41 ].…”
Section: Earthworms As Models For Environmental Stress Assessmentmentioning
confidence: 99%
“…By ingesting soil in the amount of 2 to 30 times their body weight per day, they exert a major impact on the physical, chemical, and microbiological properties of the soil and thus on the soil profile development [ 38 ]. Through their soil-dwelling activities, earthworms cause changes in nutrient availability, soil respiration, impact the composition and biomass of soil microorganisms, an abundance of other soil invertebrates, and composition of plant communities [ 39 ]. Due to their irreplaceable contribution to ecosystem goods and services, earthworms are often referred to as “ecosystem engineers”.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, soil pollution due to the use of TWW could become a problem, especially relevant when these crops are intended for human/cattle consumption but, likewise, it could also affect soil dwelling organisms. Especially relevant would be the impact on biota that play a key role in improving soil properties and considered soil engineers, such is the case of naturally occurring earthworm, with negative consequences in agriculture (Velki and Ecimovic, 2017).…”
mentioning
confidence: 99%